Immunobiology of Fibrin‐Based Engineered Heart Tissue. (6th May 2015) - Conradi, Lenard; Schmidt, Stephanie; Neofytou, Evgenios; Deuse, Tobias; Peters, Laura; Eder, Alexandra; Hua, Xiaoqin; Hansen, Arne; Robbins, Robert C.; Beygui, Ramin E.; Reichenspurner, Hermann; Eschenhagen, Thomas; et al.
Abstract : This study demonstrated that immune responses directed against a novel fibrin‐based engineered heart tissue (EHT) were primarily mediated by a Th1 response. Rejection of xenogeneic EHT matrix containing syngeneic cells was selective for the matrix, without evidence of cell rejection. Degradation of such an immunogenic matrix can be voluntarily controlled by withdrawal of temporary immunosuppression. Abstract : Different tissue‐engineering approaches have been developed to induce and promote cardiac regeneration; however, the impact of the immune system and its responses to the various scaffold components of the engineered grafts remains unclear. Fibrin‐based engineered heart tissue (EHT) was generated from neonatal Lewis (Lew) rat heart cells and transplanted onto the left ventricular surface of three different rat strains: syngeneic Lew, allogeneic Brown Norway, and immunodeficient Rowett Nude rats. Interferon spot frequency assay results showed similar degrees of systemic immune activation in the syngeneic and allogeneic groups, whereas no systemic immune response was detectable in the immunodeficient group ( p < .001 vs. syngeneic and allogeneic). Histological analysis revealed much higher local infiltration of CD3‐ and CD68‐positive cells in syngeneic and allogeneic rats than in immunodeficient animals. Enzyme‐linked immunospot and immunofluorescence experiments revealed matrix‐directed TH1‐based rejection in syngeneic recipients without collateral impairment of heart cell survival. Bioluminescence imaging was used for in vivo longitudinal monitoring of transplanted luciferase‐positive EHT constructs. Survival was documented in syngeneic and immunodeficient recipients for a period of up to 110 days after transplant, whereas in the allogeneic setting, graft survival was limited to only 14 ± 1 days. EHT strategies using autologous cells are promising approaches for cardiac repair applications. Although fibrin‐based scaffold components elicited an immune response in our studies, syngeneic cells carried in the EHT were relatively unaffected. Significance: An initial insight into immunological consequences after transplantation of engineered heart tissue was gained through this study. Most important, this study was able to demonstrate cell survival despite rejection of matrix components. Generation of syngeneic human engineered heart tissue, possibly using human induced pluripotent stem cell technology with subsequent directed rejection of matrix components, may be a potential future approach to replace diseased myocardium.